2021
DOI: 10.1177/09612033211004725
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression analysis confirms CD44 splicing impairment in systemic lupus erythematosus patients

Abstract: Background Systemic Lupus Erythematosus (SLE) is a complex chronic autoimmune disease characterized by several immunological alterations. T cells have a peculiar role in SLE pathogenesis, moving from the bloodstream to the peripheral tissues, causing organ damage. This process is possible for their increased adherence and migration capacity mediated by adhesion molecules, such as CD44. Ten different variant isoforms of this molecule have been described, and two of them, CD44v3 and CD44v6 have been found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Adhesion and migration mediated by adhesion molecules are associated with the pathogenesis of SLE, and the high expression of CD44v6 mRNA in PBMCs is correlated with disease duration ( 50 ). The mRNA expression of METTL14, ALKBH5, and YTHDF2 is increased in PBMCs of SLE patients.…”
Section: Candidate Rnas As Sle Biomarkersmentioning
confidence: 99%
“…Adhesion and migration mediated by adhesion molecules are associated with the pathogenesis of SLE, and the high expression of CD44v6 mRNA in PBMCs is correlated with disease duration ( 50 ). The mRNA expression of METTL14, ALKBH5, and YTHDF2 is increased in PBMCs of SLE patients.…”
Section: Candidate Rnas As Sle Biomarkersmentioning
confidence: 99%
“…CD44v6 has been widely confirmed as a marker of cancer with metastatic potential, and its inhibition is proving to be a therapeutic strategy [9][10][11][12]. Other isoforms have been proposed as candidate biomarkers of inflammatory processes such as allergic asthma [13], systemic lupus erythematosus (SLE) [14,15], and multiple sclerosis (MS) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been previously described a specific role of CD44 isoforms in the pathogenesis of immunomodulated diseases (Di Sante et al, 2013), whereas involvement of CD44v5 was shown in the pathogenesis of asthma (Yang et al, 2012). In addition, CD44 v3/v6 was proposed as biomarker of disease activity in systemic lupus erythematosus (SLE) (Latini et al, 2021;Novelli et al, 2019). Decrease of CD44 expression leads to a reduction of adhesive interactions with lymph node matrix, thereby facilitating the exit of T cells from lymph nodes (Brennan et al, 1997;McDonald and Kubes, 2015).…”
Section: Introductionmentioning
confidence: 99%